Crystalline polymorph of 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl]fluorene and method for producing the same

A novel crystallization process for 9,9-bis(6-hydroxyethoxy)-2-naphthyl)fluorene (BNEF) crystals addresses purity and solubility issues, resulting in high-purity, low-coloring forms with enhanced thermal stability for industrial use.

JP2025015572AActive Publication Date: 2025-01-30OSAKA GAS CHEM KK
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024196671
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-03-28
Filing Date
2024-11-11
Publication Date
2025-01-30
Estimated Expiration
2039-03-27

AI Technical Summary

Technical Problem

Existing methods for producing 9,9-bis(6-hydroxyethoxy)-2-naphthyl)fluorene (BNEF) crystals result in low purity, high coloring, residual solvents, and reduced solubility, which affect their application and handling properties.

Method used

A new crystallization process using specific solvent mixtures and conditions to produce high-purity, low-coloring crystal forms (A) and non-crystalline polymorphs (B) of BNEF, characterized by distinct X-ray diffraction patterns and minimal solvent retention.

Benefits of technology

The new crystal forms exhibit high purity, low coloring, improved solubility, and thermal stability, enabling safer and more efficient use in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015572000001_ABST
    Figure 2025015572000001_ABST
Patent Text Reader

Abstract

To provide a novel amorphous polymorph of 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl]fluorene (BNEF) with high purity and low coloration and a method for producing the same.SOLUTION: Prepared is an amorphous polymorph B, produced through the melting and cooling of crystalline polymorph A of 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl]fluorene, having diffraction peaks at diffraction angles 2θ=12.5±0.2°, 20.4±0.2°, 22.2±0.2°, 23.1±0.2°, and 25.9±0.2° in a powder X-ray diffraction pattern.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a 9,9-bis[6-(2-hydroxyphenyl)phenyl]phenyl ether compound that is colorless, has high purity, and has excellent thermal stability. New polymorphs (crystalline and amorphous polymorphs) of [2-naphthyl](methoxyethoxy)fluorene ) and a method for producing the same. [Background technology]

[0002] Compounds with a fluorene skeleton, such as 9,9-bis(hydroxyaryl)fluorenes It is known that the material has excellent properties such as high refractive index and high heat resistance. For example, JP 2011-68624 A (Patent Document 1) describes 3-mercaptopropionic acid and 9-Fluorenone and ethylene glycol mono(2-naphthyl) ether in the presence of sulfuric acid The reaction mixture was neutralized with an aqueous solution of sodium hydroxide, and xylene was added to The crystals were precipitated by washing with distilled water and cooling, filtered and dried to obtain 9,9-bis[ 6-(2-hydroxyethoxy)-2-naphthyl]fluorene (hereinafter referred to as BNEF) The purity of the crystals was 98.3% by HPLC. It is stated that the color (APHA) of a solution containing the crystals dissolved at a concentration of 30% by weight was In addition, when toluene was used instead of xylene, the purity was 99.1% and the color of the solution was It is described that the (APHA) of such a fluorene compound was 41. has a high glass transition temperature and a high refractive index, and is useful for obtaining resins such as optical materials. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-68624 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the purity, coloration, and residual solvent content of the BNEF crystals obtained by the above method are not clear. There is room for improvement in the content. For example, the BNEF crystals obtained by the above method are The coloring tends to progress under heating conditions such as melting, and the polyester is produced by using the crystals of the BNEF. When preparing terephthalic resins, the degree of coloring of the resin increases due to heating or melting during preparation. In addition, the solvent remaining in the crystals may limit the use of the crystals from a safety standpoint. This can be a factor in causing the following.

[0005] In addition, the bulk density of the BNEF crystals is low, and they require a large amount of space for transportation and storage. Furthermore, the naphthalene ring is introduced, and the measurement and handling properties are deteriorated. The benzene ring was introduced into the 9,9-bis[4-(2-hydroxyethoxy)phenyl]phenylene. Compared with [phenyl]fluorene, the BNEF crystals have low solubility in organic solvents.

[0006] Therefore, the object of the present invention is to obtain a novel polymorph (crystalline polymorph) of BNEF having high purity and low coloration. The present invention aims to provide a method for producing the same (crystalline polymorph, amorphous polymorph).

[0007] Another object of the present invention is to provide a novel polymorph of BNEF having a low residual amount of solvent and a method for producing the same. The purpose of this invention is to provide

[0008] Yet another object of the present invention is to provide a novel polymorph of BNEF which exhibits less coloration upon heating and a method for producing the same. The present invention aims to provide a manufacturing method thereof.

[0009] Another object of the present invention is to provide a BN having a high bulk density and improved solubility in organic solvents. The object of the present invention is to provide a novel polymorph of EF and a method for producing the same. [Means for solving the problem]

[0010] The present inventors have discovered that the crystal obtained by the method of Patent Document 1 (hereinafter, simply referred to as "Crystal C") In order to increase the purity of the compound, recrystallization was attempted using xylene and toluene. The fluorene compound forms an inclusion compound with a solvent such as xylene, and the resulting mixture is then dried under reduced pressure. Even after drying, about 1 to 5% by mass of the solvent remains, which sufficiently reduces the degree of coloration and improves the purity. The present inventors further conducted extensive research to achieve the above object, and as a result, As a result, BNEF has crystal polymorphs, and the fluorene compound was crystallized from a specific crystallization solvent. The result was a product with high purity, no coloring, little residual solvent, high thermal stability, and even under heating. If the temperature is higher than the melting point, polymorph A can be obtained, which is a crystalline form that can effectively prevent coloration. They discovered that when polymorph A was melted and cooled, an amorphous form of polymorph B was produced. As a result, the present invention was completed.

[0011] That is, the present invention relates to 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl ] fluorene (hereinafter sometimes referred to as BNEF) The amorphous polymorph (hereinafter sometimes simply referred to as polymorph B) The crystalline polymorph A has a diffraction angle of 2θ=12.5 in the powder X-ray diffraction pattern. ±0.2°, 20.4±0.2°, 22.2±0.2°, 23.1±0.2°, 25.9 Polymorph A has a diffraction peak at a diffraction angle of 2θ=14. Diffraction peaks at 3±0.2°, 15.5±0.2°, 17.7±0.2°, and 18.6±0.2° Furthermore, the crystalline polymorph A may have a diffraction angle 2θ=19.5±0.2. In addition, the crystal polymorph A may have diffraction peaks at 22.6±0.2°. The peak intensity at a diffraction angle 2θ=20.4±0.2° may be the largest.

[0012] The purity of the crystalline polymorph A is 97% or more, particularly 99% or more, and the melting point is 218±3°C. In addition, since polymorph A does not form an inclusion compound with the solvent, the content of the solvent (residual The solvent content is extremely small, with the solvent content being 0.2% by mass or less. When held at 280°C for 2 hours in a nitrogen gas atmosphere, the coloring in the molten state was minimal. Hue (APHA) is 50~150.

[0013] Such a crystalline polymorph A is selected from water-soluble ethers, water-soluble alcohols, and water-soluble ketones. A solvent containing at least one selected from the group consisting of ether and water-soluble alcohol is particularly preferred. It can be produced by crystallizing BNEF from a solvent.

[0014] The amorphous polymorph B has a halo characteristic of amorphous substances in a powder X-ray diffraction pattern. Such amorphous polymorph B is formed by melting and cooling BNEF. The amorphous polymorph B also shows little coloring when heated and can be prepared by heating in a nitrogen gas atmosphere. When kept at 280°C for 2 hours under atmospheric pressure, the color (APHA) in the molten state is 50 to 200. Amorphous polymorph B has a high bulk density, 0.9-1.25 g / ml.

[0015] In addition, amorphous polymorph B, like crystalline polymorph A, has high purity and an extremely low residual solvent content. Such amorphous polymorph B has high solubility and can be used in reaction systems using solvents. This allows smooth charging and reaction. Effect of the Invention

[0016] The crystalline polymorph A of the BNEF of the present invention has high purity and little coloring. It also has excellent thermal stability, e.g. For example, it has high storage stability at high temperatures, and coloring can be significantly suppressed even when stored under heating. For example, coloring can be effectively suppressed even at a temperature equal to or higher than the melting point. Both the amorphous polymorph B and amorphous polymorph B have a low residual amount of solvent, making them highly safe and suitable for a wide range of applications. Furthermore, the amorphous polymorph B has a high bulk density, which improves the handling properties. Furthermore, the amorphous polymorph B has high purity and is excellent in solubility in organic solvents. It contains amorphous polymorphs that have little coloring and can significantly suppress coloring even when stored under heat. Therefore, the crystalline polymorph A and amorphous polymorph B are highly safe and can be used in industrial products and organic chemicals. It can be used in a wide range of applications, including as a compound, a resin raw material, or a resin hardener. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a chart showing the powder X-ray diffraction pattern of Crystal C obtained in Comparative Example 1. [Diagram 2] FIG. 2 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph A1 obtained in Example 1. [Diagram 3] FIG. 3 is a chart showing the powder X-ray diffraction pattern of the amorphous polymorph B1 obtained in Example 2. [Figure 4] FIG. 4 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph A2 obtained in Example 4. [Diagram 5] FIG. 5 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph A3 obtained in Example 5. [Figure 6] FIG. 6 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph A4 obtained in Example 6. [Figure 7] FIG. 7 is a chart showing the powder X-ray diffraction pattern of the crystalline polymorph A5 obtained in Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] [Polymorph] The polymorph A of the crystalline form of the present invention is 9,9-bis[6-(2-hydroxyethoxy)-2 1. Crystal polymorph of BNEF, having a powder X-ray diffraction pattern (X RD), the diffraction angles 2θ = 12.5 ± 0.2°, 20.4 ± 0.2°, and 22.2 ± It has characteristic diffraction peaks at 0.2°, 23.1±0.2°, and 25.9±0.2°. In addition, the diffraction angle 2θ is preferably 14.3±0.2°, 15.5±0.2°, 17.7±0.2°, It is more preferable that the diffraction peaks are at the diffraction angles of 18.6±0.2° and 18.6±0.2°. There are also diffraction peaks at angles 2θ=19.5±0.2° and 22.6±0.2°.

[0019] In addition, polymorph A has diffraction angles 2θ=7.7±0.2°, 8.8±0.2°, and 1 1.1±0.2°, 11.4±0.2°, 12.9±0.2°, 13.8±0.2°, 1 6.9±0.2°, 17.4±0.2°, 21.2±0.2°, 24.7±0.2°, 2 At least one diffraction angle 2θ selected from 5.4±0.2° and 26.7±0.2° Of these 12 diffraction angles 2θ, the diffraction peaks are preferably Folding angle 2θ=7.7±0.2°, 11.1±0.2°, 11.4±0.2°, 24.7± 0.2°, 25.4±0.2°, 26.7±0.2°. More preferably, the diffraction angle 2θ is 24.7±0.2°, 25.4 Diffraction peaks at at least one selected from 26.7±0.2° and 26.7±0.2°. Of these 12 diffraction angles 2θ, preferably, at least at least three, at least six, at least nine diffraction peaks at the diffraction angle 2θ; Preferably, it has at least diffraction peaks at all 12 diffraction angles 2θ.

[0020] Polymorph A may have the above diffraction peak pattern. Generally, in polymorph A, Peak intensity I at diffraction angle 2θ = 20.4 ± 0.2° 15 (integrated intensity I 15s and peak Height I 15h ) is the largest, followed by the integrated intensity at a diffraction angle of 2θ = 12.5 ± 0.2°. I 5s , the integrated intensity I at 22.2±0.2° 17s , the integrated intensity I at 22.6±0.2° 18s , the integrated intensity at 23.1±0.2° I 19s , the integrated intensity I at 25.9±0.2° 22s The integrated intensity at at least one diffraction angle 2θ selected from the above is large. Of the minute intensities, I 15s The second largest integrated intensity after 5s , I 17s and I1 8s and preferably I 17s or I1 8s , more preferably I 18sIt is more pure and less colored, so it is more suitable for integral strength. The order of degrees is I 15s ≫I 18s ≧I 19s ,I 17s ,I 22s ,I 5s The order is It is preferable that 15s ≫I 18s ≧I 19s ,I 17s ,I 22s ≧ I 5s The order is particularly preferably I 15s ≫I 18s ≧I 19s ≧I 17s ≧I 22 s ≧I 5s In the description of the order, for example, "I 18s ≧I 19s ,I 17s ,I 22s ≧I 5s " is I 19s ,I 17s and I 22s Both are I1 8s Less than or equal to, and I 5s It means that it is equal to or greater than the specified value. 19s ,I 17s ,I 22s The order between them is not particularly limited.

[0021] Polymorph A usually has a diffraction peak at a diffraction angle 2θ=20.4±0.2° and the diffraction peaks shown in Table 1 below. In addition, in polymorph A, the diffraction peaks at the diffraction angle Integral intensity I at 2θ=20.4±0.2° 15s and peak intensity (peak height) I 15 h When the value is set to "100", the integrated intensity and peak intensity (peak height) are shown in Table 1 below. and preferably has the powder X-ray diffraction pattern shown in FIG.

[0022] [Table 1]

[0023] Polymorph A has a diffraction peak at a diffraction angle 2θ=20.4±0.2° and the diffraction peak shown in Table 1 above. In most cases, the diffraction peak is at least 2θ=6.5±0. .2°, 8.3±0.2°, 9.9±0.2°, 16.3±0.2°, 16.4±0.2 °, 16.7±0.2°, 18.7±0.2°, 19.8±0.2°, 20.3±0.2 °, 22.3±0.2°, 23.0±0.2°, 23.9±0.2°, 24.1±0.2 26.4±0.2°, 26.9±0.2°, or one or more diffraction angles 2θ selected from the group consisting of Among these diffraction peaks, at least one having a diffraction angle of 2 θ=16.3±0.2°, 18.7±0.2°, 20.3±0.2°, 22.3±0.2 Diffraction peaks are set at at least one selected from 23.9±0.2°, 23.9±0.2°, and 26.9±0.2°. It is preferred that the conductor has a peak.

[0024] The above powder X-ray diffraction pattern can be measured using a conventional powder X-ray diffractometer. The diffraction angle 2θ, which indicates the peak, varies by about ±0.2° or ±0.1° depending on the measurement conditions. This may be the case.

[0025] The crystalline polymorph A of the present invention has a high purity, for example, 97% or more, preferably 98% or more, and more preferably 97% or more. More preferably, the purity of the crystalline polymorph A is in the range of 98 to 100%. The preferred ranges are as follows: 98.5 to 99.95%, 99 ~99.9%, 99.3~99.9%, and 99.5~99.9%. The purity is usually 99 to 100%. The purity can be calculated by HPLC analysis.

[0026] The melting point of the crystalline polymorph A is, for example, 21° C. when measured by a differential scanning calorimeter (DSC). 8±4°C, preferably 218±3°C, and more preferably 218±2°C. Polymorph A has excellent storage stability, especially at high temperatures. It can be measured based on the endothermic peak (or melting point) in differential scanning calorimetry (DSC).

[0027] Such a crystalline polymorph A has a small content (residual amount) of solvent. The residual solvent amount is, for example, 0.2% by mass or less, preferably 0.15% by mass or less, and more preferably 0.1% by mass or less The amount of the remaining solvent can be measured based on gas chromatography.

[0028] The bulk density of the crystalline polymorph A may be, for example, about 0.3 to 1 g / ml, and is preferably The ranges are as follows: 0.4-0.9g / ml, 0.5-0.8g / ml, 0. The bulk density is preferably 53 to 0.7 g / ml, and more preferably 0.55 to 0.65 g / ml. It can be measured by the bulk density measurement method specified in the Japanese Pharmacopoeia.

[0029] The crystalline polymorph A of the present invention can effectively suppress coloration even when stored at high temperatures, and the crystalline polymorph A described in the Examples can be effectively suppressed from coloring even when stored at high temperatures. As shown above, even if the sample is kept at 280℃ for 2 hours under a nitrogen gas atmosphere, the color of the sample in the molten state (A PHA) may be, for example, about 30 to 200, and the preferred range is as follows: The steps are 40~180, 50~150, 75~125, and 80~120.

[0030] The crystal obtained by the method of Patent Document 1 (Crystal C) was powder X, as shown in FIG. In the X-ray diffraction pattern, the diffraction angles 2θ=13.8±0.2°, 16.4±0.2°, 1 Specially for 9.5±0.2°, 20.5±0.2°, 22.5±0.2°, and 26.2±0.2° The diffraction angles 2θ=12.1±0.2°, 13.0±0.2°, and 14. 6±0.2°, 19.8±0.2°, 20.0±0.2°, 21.8±0.2°, 24. A peak may also be observed at 2θ=13.8±0.2°, 20.5± The peak at 0.2° is often large, and the peak height at 13.8±0.2° is the largest. Such a powder X-ray diffraction pattern is similar to the diffraction pattern of the crystalline polymorph A. This is very different from the previous version.

[0031] The crystalline polymorph A is at least one selected from the group consisting of ethers, alcohols, and ketones. From a solvent containing 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl] It can be prepared by crystallizing benzyl fluorene (BNEF). The crystallization solvent is highly polar. It is preferable that the crystallization solvent is composed of water-soluble solvents. Usually, all the solvents constituting the crystallization solvent are water-soluble solvents ( or an aqueous solvent). Solubility of water-soluble solvents (or aqueous solvents) such as alcohols, water-soluble ketones, etc. in water is the solubility of the crystallization solvent in water] is, for example, 1 g / L or more (e.g., 10 g / L or more), preferably 100 g / L or more (e.g., 200 g / L or more), and more preferably Preferably, it is 300 g / L or more (e.g., 500 g / L or more), and in particular, it is any concentration for water. It is preferable that the solubility in water is too low, and the pure The strength may decrease or the glass may become easily discolored.

[0032] Examples of the ether include cyclic ethers such as dioxane and tetrahydrofuran. Examples of dioxane include 1,3-dioxane and 1,4-dioxane. Water-soluble ethers are often used as ethers. Dioxanes such as 4-dioxane are preferred.

[0033] As the alcohol, a water-soluble alcohol is usually used. Examples of the solvent include methanol, ethanol, propanol, and isopropanol. Preferred water-soluble alcohols are methanol and ethanol, and methanol is usually used. It is often used.

[0034] The ketones include acetone, methyl ethyl ketone (MEK), methyl propyl ketone (MKE), ketone, methyl isopropyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl Luketone etc. C 3-8 Examples of the ketone include water-soluble ketones. Of these ketones, C 3-6 Ketones are preferred, as they have high purity and little coloring. From the point of view of C 3-5 Ketones are more preferred, acetone or MEK are even more preferred, and acetone is Ton is particularly preferred.

[0035] These solvents can be used alone or in combination as a mixed solvent of two or more kinds. Among these solvents, water-soluble ether and other ether-based solvents, water-soluble ketones, etc. A single solvent of any ketone or a mixed solvent of ether and alcohol is preferred. A mixed solvent of an ether and a water-soluble alcohol is preferred.

[0036] Mass ratio of ether such as 1,4-dioxane to water-soluble alcohol such as methanol For example, the former / latter ratio is 90 / 10 to 10 / 90, preferably 80 / 20 to 20 / 80. More preferably, it is 70 / 30 to 30 / 70, and particularly preferably 60 / 40 to 40 / 60. By adjusting the ratio of a good solvent, ether, to a poor solvent, such as water-soluble alcohol, such as methanol, As a result, it is possible to obtain high-quality crystalline polymorph A in high yield.

[0037] In addition, when the crystallization solvent is a mixed solvent, it is highly polar or highly water-soluble (or highly miscible with water). As long as the above-mentioned ethers, alcohols and ketones are not included, other solvents may be used as long as they do not impair the properties of the reaction system. The other solvent may be a conventional polar solvent (or a water-soluble solvent). These other solvents may be used alone or in combination of two or more. It can also be used.

[0038] Examples of the non-polar solvent include hydrocarbons. For example, aliphatic hydrocarbons, specifically, C hexane, heptane, octane, etc. 4- 12 Aliphatic hydrocarbons; alicyclic hydrocarbons, specifically, C such as cyclohexane 5-1 0 Aliphatic hydrocarbons; aromatic hydrocarbons, specifically, benzene, alkylbenzene, etc. C 6-10 These non-polar solvents may be used alone or in combination with other solvents such as aromatic hydrocarbons. Two or more of these non-polar solvents may be used in combination. The elements are preferred.

[0039] The alkylbenzene may be toluene, xylene, ethylbenzene, trimethylbenzene, or the like. Mono- or tetra-C such as benzene, ethyltoluene, propylbenzene, and cumene 1-4 a Among these aromatic hydrocarbons, alkylbenzenes and alkyl-benzenes are Preferred are mono- or tri-C 1-3 Alkyl-benzenes, more preferably Or Mono or DiC 1-2 Alkyl-benzenes, especially toluene or xylose. Of these, toluene is preferred, and toluene is particularly preferred.

[0040] When the above-mentioned other solvents such as aromatic hydrocarbons are contained, the ratio of the other solvents to the total crystallization solvent is as follows: For example, it may be about 0.1 to 49.9 mass %, and the preferred range is as follows: 1-45% by mass, 5-40% by mass, 10-35% by mass, 15-33% by mass, 20-3 From the viewpoint of purity and ease of suppressing coloration, other solvents such as non-polar solvents are not used. Therefore, the ratio of other solvents such as non-polar solvents should be smaller than the total crystallization solvent. For example, the amount may be less than 50% by mass, usually about 0 to 40% by mass, and is preferably The range is as follows: 30% by mass or less, 20% by mass or less, 10% by mass or less, 5% by mass or less. % by mass or less, more preferably 0% by mass, i.e., substantially no other solvent is contained. It is preferable.

[0041] The ratio (or amount) of the crystallization solvent is not particularly limited. 0.1 to 20 parts by mass, preferably 0.5 to 15 parts by mass, based on 1 part by mass (calculated as min) The amount is preferably 1 to 10 parts by mass, particularly preferably 3 to 8 parts by mass, and especially preferably 4 to 5 parts by mass.

[0042] The crystalline polymorph A is obtained by supersaturating the fluorene compound (BNEF) in the crystallization solvent. The BNEF can be precipitated by dissolving it in the crystallization solution and cooling it. Polymorph A can be precipitated or crystallized by heating, dissolving in a solvent, and then cooling. After dissolution, the solvent may be distilled off under reduced pressure as necessary to adjust the amount of the crystallization solvent to fall within the above ratio range. The BNEF may be prepared by the method described in Patent Document 1. ,9-bis[6-hydroxy-2-naphthyl]fluorene, ethylene oxide added a method of reacting ethylene carbonate and / or 2-chloroethanol, etc. It may be prepared by any conventional method. BNEF may also be prepared, for example, by conventional methods. The isolated fluorene compounds, whether in crystalline form such as crystalline C or in amorphous form, The product may be dissolved in the crystallization solvent and crystallized. After completion of the reaction, the solvent in the reaction mixture may be replaced with the crystallization solvent to crystallize the crystalline polymorph A. For example, in the case of reaction mixtures and separation, solvents are removed from the organic phase, including toluene and xylene. The residue may be dissolved in the crystallization solvent to crystallize the crystalline polymorph A.

[0043] The temperature at which the BNEF is dissolved in the crystallization solvent is a temperature lower than the boiling point of the solvent, for example, 30 The cooling temperature is not particularly limited, and the final cooling temperature is For example, the temperature is from -10°C to 30°C, preferably from 1°C to 20°C, and more preferably from 5°C to 15°C. Although rapid cooling is possible, it is usually allowed to cool naturally or slowly.

[0044] In the crystallization procedure, seed crystals may be added if necessary, and the crystallization procedure may be carried out in one go. In particular, in the present invention, the crystallization can be carried out in one crystallization operation. The high purity and colorless crystalline polymorph A, i.e., the crystalline polymorph A having the above-mentioned APHA, It can be generated.

[0045] The generated crystals are usually separated by a separation means such as filtration or centrifugation, and then dried. As a result, it is possible to obtain crystalline polymorph A having high purity and little coloration and residual solvent.

[0046] The amorphous polymorph B of the present invention has a powder X-ray diffraction pattern as shown in FIG. , exhibits a halo peak characteristic of amorphous substances and does not exhibit a melting point. Such amorphous polymorph B is The block may be a powder or granule pulverized to any particle size. The block may have a bulk density ( The density is high, for example, 0.9 to 1.25 g / ml, preferably 0.95 to 1.22 g / ml. The density is preferably 1 to 1.2 g / ml, and more preferably 1 to 1.2 g / ml. The excluded volume of the block is calculated from the mass and volume of the block. In addition, polymorph B is non-crystalline or amorphous and has a high bulk density, making it difficult to transport, store, and transport. The tube space can be reduced, and measurement and handling are improved, while the compatibility with organic solvents is improved. Therefore, it can be dissolved quickly in the solution reaction system, and the raw material can be easily charged and reacted. The bulk density of the powder or granule depends on the particle size. The bulk density may be the same as that of the crystalline polymorph A, and may be 0.1 to 0.6 g / ml. The granular amorphous polymorph B has even greater solubility in organic solvents.

[0047] Furthermore, polymorph B, like polymorph A, has a low solvent content (residual amount) and The amount is, for example, 0.2% by mass or less, preferably 0.15% by mass or less, and more preferably 0. Less than 0.1% by mass.

[0048] Even if such polymorph B is produced through a melting process as described below, it is possible to obtain the same results as polymorph A. The purity is high, for example, 97% or more, preferably 98% or more, and more preferably 99% or more. The purity of polymorph B is usually 98-99.99%, preferably 98.5-99. The purity of polymorph B is usually 99 to 100%, more preferably 95%. 00%.

[0049] The polymorph B of the present invention, like the polymorph A, can effectively suppress coloration even when stored at high temperatures. As mentioned above, even if the material is kept at 280°C for 2 hours under a nitrogen gas atmosphere, the color of the molten material (A PHA) is, for example, in the range of 50 to 200, and the preferred range is as follows: , 70~180, 80~170, 100~150, and 110~140.

[0050] The amorphous polymorph B can be obtained by melting and cooling the crystalline or amorphous form of BNEF. When a crystalline form of BNEF is used, the amorphous polymorph B can be prepared by The polymorph B1 may be prepared by melting and cooling the polymorph A, and the crystalline form C may be The polymorph B1 may be prepared by melting and cooling As mentioned above, it has high purity, little coloring (including coloring at high temperatures), and low solvent content (residual amount) In contrast, polymorph B2 is less pure than polymorph B1 and is stored at high temperatures. When heated, it tends to be more colored than polymorph B1.

[0051] Amorphous polymorph B is formed by heating BNEF crystals above the melting point. For example, crystalline polymorph A is Heat to 220-300℃, especially 230-280℃, melt, and then cool (or rapidly cool, leave to cool, slowly The resulting mass can be crushed, classified, etc., if necessary. It may be in the form of powder or granules of a given size. EXAMPLES

[0052] The present invention will be described in more detail below with reference to examples. The evaluation methods used in the examples and reference examples are as follows: It is.

[0053] (X-ray diffraction (XRD)) Powder X-ray diffraction device (“Fully automatic multi-purpose horizontal X-ray diffraction device Smart Lab”, manufactured by Rigaku Co., Ltd.) ) was used, and measurements were taken under conditions of 3 kW output, radiation source (Cu tube), and measurement angle of 5 to 70°.

[0054] (Melting Point) A differential scanning calorimeter (EXSTAR DSC6200, manufactured by SII NanoTechnology Co., Ltd.) was used. The measurements were performed under a nitrogen atmosphere at a measurement temperature of 30 to 300° C. and a temperature rise rate of 10° C. / min.

[0055] (purity) High performance liquid chromatography (HPLC) equipment (Shimadzu Corporation "LC-2010A HT") The measurement was carried out under the following conditions using a gel ("TSKgel ODS-80TM" manufactured by Tosoh Corporation).

[0056] Detection method: UV, detection wavelength 254 nm Column temperature: room temperature Eluent (volume ratio): acetonitrile / 0.1% phosphoric acid aqueous solution = 55 / 45 → 95 / 5(gradient) Flow rate: 1.0ml / min.

[0057] (Hue APHA) 20g of sample was placed in a test tube, heated to 280℃ in a nitrogen atmosphere and held for 2 hours. (Melted sample) was measured using a color difference turbidity meter ("COH- The hue was measured using a "Nippon Denshoku 300A" lamp.

[0058] (Bulk density and density) The bulk density was measured according to the bulk density measurement method of the Japanese Pharmacopoeia. The excluded volume of the block was determined using a cylinder, and the weight and volume of the block were calculated. .

[0059] (Residual Solvent Amount) The sample was dried under reduced pressure at 120°C overnight, then dissolved in tetrahydrofuran and analyzed by gas chromatography. GC equipment (Shimadzu Corporation "GC-2014", column: CBP-1, detector: F The amount of remaining solvent was measured at a measurement temperature range of 50 to 290°C.

[0060] Comparative Example 1: Crystal C of Patent Document 1 Crystal C was obtained according to Example 13 of Patent Document 1. In a flask, 45 g of 9-fluorenone (0.25 mol, manufactured by Osaka Gas Chemicals Co., Ltd.) Ethylene glycol mono(2-naphthyl) ether 235g (1 mole, Meisei Chemical Co., Ltd.) ), add 1g of 3-mercaptopropionic acid, and then heat to 60℃ until completely dissolved. After that, 54 g of sulfuric acid was gradually added and the mixture was stirred for 6 hours at 60°C. The conversion rate of 9-fluorenone was confirmed to be 99.5% or more by HPLC. The reaction liquid was neutralized by adding 48% by weight of caustic soda solution, and then 400 g of xylene was added. The organic phase was washed several times with distilled water and then cooled to precipitate crystals. After further filtration and drying at 120°C, 114g (yield 85%) of crystalline C (white ) was obtained. 1 As a result of H-NMR measurement, the target 9,9-biphenyl It was found that the compound was bis[6-hydroxy(2-hydroxyethyl)-2-naphthyl]fluorene. Confirmed.

[0061] The powder X-ray diffraction pattern of the obtained crystalline C is shown in FIG.

[0062] X-ray diffraction peak (relative integrated intensity; relative peak height in parentheses): diffraction angle 2θ=6 .46°(3.5;4.5), 8.33°(16.2;12.2), 10.14°(16 .6;11.6), 10.98°(27.2;21.9), 12.06°(30.7;4 1.4), 13.00°(24.4;31.4), 13.76°(76.9;100.0 ), 14.59°(29.1;37.1), 16.04°(33.0;12.5), 16 .43°(41.1;41.3), 16.73°(13.7;8.2), 17.92°( 19.5;21.0), 18.26°(16.9;14.0), 19.53°(41.3 ;61.6), 19.78°(58.7;58.1), 20.04°(27.1;36. 8), 20.46°(100.0;75.2), 21.39°(33.3;40.0), 21.82°(67.9;51.3), 22.59°(63.8;32.5), 24.1 5°(63.3;51.7), 24.82°(38.4;36.6), 26.27°(7 1.9;53.1).

[0063] The melting point of the obtained crystal C was 203°C, the purity was 95.5%, and the bulk density was 0.4g / ml. The color (APHA) of the sample in the heated and molten state (yellow) is 500 or more, and the remaining solvent is The amount of silane was 2.7% by mass.

[0064] Example 1: Crystalline polymorph A1 In Comparative Example 1, the organic phase (xylene phase) after adding and mixing xylene was washed with distilled water. After washing, the solvent was distilled off under reduced pressure. The residue was dissolved in a 1,4-dioxane-methanol mixed solvent (1,4- Dioxane / methanol (mass ratio) = 50 / 50 (hereinafter referred to as DOX-MeOH)6 The mixture was redissolved in 00 g of water by heating to 70°C, and then cooled to 10°C to precipitate crystals. After filtering and drying at 120°C, 94 g (yield 70%) of crystalline A1 was obtained. .

[0065] The powder X-ray diffraction pattern of the obtained crystalline A1 is shown in FIG.

[0066] X-ray diffraction peak (relative integrated intensity; relative peak height in parentheses): diffraction angle 2θ = 7.66°(23.9;27.8), 8.83°(14.0;14.4), 11.12° (20.1;17.2), 11.40°(23.2;25.5), 12.48°(41. 6;43.4), 12.94°(6.9;7.6), 13.79°(13.6;15.5) ), 14.29°(36.8;38.9), 15.54°(33.2;37.4), 16 .30°(8.3;10.0), 16.89°(18.2;20.4), 17.39°( 6.1;12.2), 17.70°(35.7;40.3), 18.55°(29.4; 26.2), 18.70°(14.8;24.2), 19.53°(34.7;36.3) ), 20.28°(22.0;24.3), 20.37°(100.0;100.0), 21.18°(13.4;19.4), 22.17°(48.0;39.7), 22.3 0°(11.4;19.3), 22.62°(63.0;76.6), 23.13°(4 9.9;41.5), 23.93°(13.1;11.5), 24.73°(26.1; 28.7), 25.38°(28.2;33.0), 25.90°(45.0;38.0) ), 26.74°(25.7;36.2), 26.94°(17.3;23.0).

[0067] The melting point of the obtained crystal A1 was 219°C, the purity was 99.8%, and the bulk density was 0.6 g / ml. The color (APHA) of the sample in the molten state (colorless and transparent) was 102, and the remaining solvent The amount was 0.1% by mass or less.

[0068] Example 2: Amorphous Polymorph B1 The crystalline polymorph A obtained in Example 1 was placed in a three-neck flask and heated to 250°C under reduced pressure. When the mixture was melted and then rapidly cooled to room temperature (20 to 25°C), a mass was obtained.

[0069] The lump was crushed and the powder X-ray diffraction pattern of the powder sample is shown in FIG.

[0070] As is clear from FIG. 3, a halo peak characteristic of an amorphous material was observed, and the sample did not show a melting point. The purity of the obtained solid was 99.8%, the bulk density was 1.2 g / ml, and the melting point of the solid was 1.0 g / ml. The color (APHA) of the sample (colorless and transparent) was 131, and the residual solvent content was 0.1% by mass. The results were as follows.

[0071] Example 3: Amorphous Polymorph B2 The crystals C obtained in Comparative Example 1 were placed in a three-neck flask and heated to 250°C under reduced pressure to melt them. When the mixture was cooled rapidly to room temperature (20-25°C), a mass was obtained.

[0072] As in Example 2, the lump was crushed and the powder X-ray diffraction pattern of the powder sample was measured. As shown in FIG. 3, no halo peak was observed. The aggregates also showed no melting point. The purity of the solid obtained was 95.5%, the bulk density was 1.1 g / ml, and the melted state The hue (APHA) of the sample (yellow transparent) is 500 or more, and the residual solvent content is 0.1% or less by mass. It was below.

[0073] Example 4: Crystalline polymorph A2 In Example 1, 600 g of 1,4-dioxane-methanol mixed solvent (1,4-dioxane Instead of 1,4-dioxane / methanol (mass ratio = 50 / 50), 420 g of 1,4-dioxane The same procedure as in Example 1 was repeated except for using 1, and 81 g (60% yield) of BNEF crystals A2 was obtained. Ta.

[0074] The powder X-ray diffraction pattern of the obtained crystalline A2 is shown in FIG.

[0075] X-ray diffraction peak (relative integrated intensity; relative peak height in parentheses): diffraction angle 2θ = 7.63°(26.5;35.3), 8.81°(28.0;28.7), 11.06° (13.0;15.5), 11.34°(19.5;22.0), 12.44°(58. 8;58.5), 12.90°(5.8;6.7), 13.73°(21.4;24.3) ), 14.24°(75.1;82.9), 15.47°(29.8;33.4), 16. 24°(11.4;14.6), 16.84°(22.6;19.2), 17.36°( 16.5;14.7), 17.68°(57.2;68.0), 18.60°(32.0 ;28.5), 19.48°(59.4;65.0), 20.30°(100.0;10 0.0), 21.16°(15.4;12.6), 22.09°(99.1;84.4) , 22.59°(73.2;77.6), 23.06°(42.4;37.2), 24. 10°(19.9;16.8), 24.68°(43.5;46.1), 25.33°( 31.8;33.5), 25.86°(42.6;35.7), 26.69°(59.4 ;67.7), 26.89°(20.5;18.8).

[0076] The melting point of the obtained crystal A2 was 221°C, the purity was 99.6%, and the bulk density was 0.8g / ml. The color (APHA) of the sample in the molten state (colorless and transparent) was 107, and the remaining solvent The amount was 0.1% by mass or less.

[0077] Example 5: Crystalline polymorph A3 In Example 1, 600 g of 1,4-dioxane-methanol mixed solvent (1,4-dioxane Instead of methyl ethyl ketone / methanol (mass ratio = 50 / 50), 800 g of methyl ethyl ketone was used. The same procedure as in Example 1 was repeated except that ethyl ketone (MEK) was used to obtain 74 g of BNEF crystals A3 (yield: 55%) was obtained.

[0078] The powder X-ray diffraction pattern of the obtained crystalline A3 is shown in FIG.

[0079] X-ray diffraction peak (relative integrated intensity; relative peak height in parentheses): diffraction angle 2θ = 7.60°(11.6;11.5), 8.79°(18.7;17.4), 11.07° (27.5;23.5), 11.35°(25.2;24.6), 12.44°(59. 1;57.3), 12.90°(8.7;9.0), 13.72°(12.5;13.8 ), 14.24°(45.8;47.7), 15.47°(35.0;37.6), 16 .25°(10.1;12.5), 16.82°(22.1;22.2), 17.35° (22.1;17.6), 17.66°(40.0;43.7), 18.54°(29. 0;25.8), 18.67°(12.5;20.3), 19.47°(41.7;46 .2), 20.29°(100.0;100.0), 21.27°(19.1;11.5 ), 22.09°(62.0;49.2), 22.30°(11.4;18.4), 22 .57°(69.0;80.4), 23.05°(48.8;42.4), 23.89° (10.9;12.4), 24.66°(25.4;28.1), 25.32°(26. 4;28.3), 25.86°(47.8;38.7), 26.69°(32.8;39 .2), 26.88°(16.8;16.1).

[0080] The melting point of the obtained crystal A3 was 220°C, the purity was 99.7%, and the bulk density was 0.7g / ml. The color (APHA) of the sample in the molten state (slightly pale yellow) was 163, and the remaining molten The amount of the catalyst was 0.1% by mass or less.

[0081] Example 6: Crystalline polymorph A4 In Example 1, 600 g of 1,4-dioxane-methanol mixed solvent (1,4-dioxane Instead of 1000 g of acetone (50 / 50 mass ratio of oxane / methanol), The residue was dissolved by heating to 55°C, and 400 g of acetone was removed from the resulting solution by vacuum distillation. The same procedure as in Example 1 was repeated except for cooling to 10° C. to obtain 67 g of BNEF crystals A4 (yield 50%) was obtained.

[0082] The powder X-ray diffraction pattern of the obtained crystalline A4 is shown in FIG.

[0083] X-ray diffraction peak (relative integrated intensity; relative peak height in parentheses): diffraction angle 2θ = 7.61°(10.7;10.3), 8.80°(17.5;17.2), 11.09° (19.6;17.4), 11.36° (19.4;21.1), 12.45° (61. 1;63.0), 12.90°(6.6;7.5), 13.74°(12.0;14.6) ), 14.25°(51.5;55.7), 15.49°(27.8;31.6), 16 .27°(9.2;12.8), 16.83°(18.0;18.8), 17.37°( 19.3;14.6), 17.67°(41.6;45.5), 18.54°(12.3 ;11.0), 18.64°(25.2;29.0), 19.49°(45.8;50. 4), 20.32°(100.0;100.0), 21.17°(11.6;13.9) , 22.12°(51.4;49.3), 22.27°(25.4;20.5), 22. 59°(57.9;74.2), 23.09°(43.2;34.9), 23.91°( 9.9;11.0), 24.70°(26.8;29.2), 25.35°(23.3; 26.6), 25.87°(40.3;33.3), 26.70°(33.8;42.7) ), 26.91°(12.5;13.4).

[0084] The melting point of the obtained crystal A4 was 220°C, the purity was 99.5%, and the bulk density was 0.4 g / ml. The color (APHA) of the sample in the molten state (light yellow) was 141, and the amount of remaining solvent was was 0.1 mass % or less.

[0085] Example 7: Crystalline polymorph A5 In Example 1, 600 g of 1,4-dioxane-methanol mixed solvent (1,4-dioxane Instead of 600g of methyl isobutyl ether (mass ratio: 50 / 50), Ketone (MIBK)-toluene mixed solvent (MIBK / toluene (mass ratio) = 75 / 25, The same procedure as in Example 1 was repeated except that B was used. 105 g (78% yield) of NEF crystals A5 was obtained.

[0086] The powder X-ray diffraction pattern of the obtained crystalline A5 is shown in FIG.

[0087] X-ray diffraction peak (relative integrated intensity; relative peak height in parentheses): diffraction angle 2θ = 6.47°(9.9;16.0), 7.61°(33.5;54.8), 8.25°(3 .6;3.5), 8.80°(13.9;14.9), 9.87°(6.5;8.5), 11.10°(20.8;19.3), 11.38°(13.1;16.3), 12.4 5°(45.3;52.3), 12.95°(20.1;22.9), 13.76°(2 8.3;28.0), 14.28°(41.2;54.0), 15.48°(17.5; 24.4), 16.42°(7.7;13.4), 16.85°(14.2;18.0) , 17.38°(6.8;12.6), 17.69°(29.1;38.3), 18.5 5°(26.8;25.7), 19.51°(45.6;51.3), 19.81°(3 4.5;29.4), 20.31°(100.0;100.0), 21.16°(5.9 ;10.8), 22.12°(56.7;56.1), 22.29°(18.5;26. 0), 22.59°(63.1;83.1), 23.01°(17.1;17.3), 2 3.11°(18.0;31.2), 24.14°(30.9;26.6), 24.67 °(28.6;33.5), 25.35°(24.0;28.7), 25.87°(27 .6;27.0), 26.36°(17.0;14.5), 26.72°(45.3;5 9.1).

[0088] The melting point of the obtained crystal A5 was 216°C, the purity was 99.3%, and the bulk density was 0.4g / ml. The hue (APHA) of the sample in the molten state (light yellow) was 182, and the amount of remaining solvent was , was 0.1 mass % or less.

[0089] The properties of the polymorphs obtained in Comparative Example 1 and Examples 1 to 7 are shown in Table 2.

[0090] [Table 2]

[0091] As can be seen from Table 2, the crystalline polymorphs A1 to A5 have high melting points, high purity, and little residual solvent. Polymorph B1 also has high purity and little residual solvent. It does not discolor easily when heated and melted at high temperatures. It also has a high bulk density. Polymorph B1 has less residual solvent and a higher bulk density than crystalline C. [Industrial Applicability]

[0092] The polymorph of the present invention has little coloring, high purity, and a small amount of residual solvent. It can be suitably used as a raw material for industrial products, organic synthesis, and resin synthesis. The compound has a bis(hydroxynaphthyl)fluorene structure, which gives it a variety of properties (optical properties, etc.). , heat resistance, water resistance, moisture resistance, chemical resistance, electrical properties, mechanical properties, dimensional stability, etc. Therefore, the polymorph of the present invention can be suitably used as a resin raw material, a resin curing agent, etc. In particular, the polymorph of the present invention can be used in the manufacture of thermosetting resins [epoxy resins (or their curing agents) and , acrylic resins (multifunctional (meth)acrylates, etc.), thermoplastic resins (polyethylene When applied to styrene resins, polyurethane resins, etc., it has high heat resistance, high crosslinking properties, high refractive index, The epoxy resin can efficiently impart excellent properties such as transparency and low linear expansion coefficient. It is suitable for applications requiring such properties, such as semiconductor encapsulation and electrical substrates. The acrylic resin is also useful for optical materials, for example, as an optical overcoat agent, a hard coat agent, etc. Useful for hard coatings, anti-reflective films, eyeglass lenses, optical fibers, optical waveguides, holograms, etc. The thermoplastic resin is also useful as a molding material for optical components, heat-resistant components, etc. Can be used.

Claims

1. Amorphous polymorph B is a melt-cooled product of crystalline polymorph A of 9,9-bis[6-(2-hydroxyethoxy)-2-naphthyl]fluorene, which has diffraction peaks at diffraction angles 2θ=12.5±0.2°, 20.4±0.2°, 22.2±0.2°, 23.1±0.2°, and 25.9±0.2° in a powder X-ray diffraction pattern.

2. 2. The polymorph B of claim 1 having a bulk density of 0.9 to 1.25 g / ml.

3. 3. Polymorph B according to claim 1 or 2, having a residual solvent content of 0.2% by weight or less.

4. 4. Polymorph B according to any one of claims 1 to 3, having a purity of 97% or more.

5. A method for producing the amorphous polymorphic form B according to any one of claims 1 to 4, comprising melting and cooling said crystalline polymorphic form A.

Citation Information

Patent Citations

  • Crystal polymorph of fluorene derivative and method for producing the same

    JP2008222708A

  • Alcohol having fluorene skeleton

    JP2009155253A

  • Epoxy compound having fluorene skeleton

    JP2009155256A

  • Method for producing fluorene skeleton-containing alcohol

    JP2011068624A

  • Amorphous form of fluorene derivative and method for producing the same

    JP2015098458A